HLA typing in patients with recurrent aphthous stomatitis - Taghavi Zenouz A; Sobuti R; Jafari Sh; Nikbin B (Tehran University of Medical Sciences, 2004)
Recurrent aphthous stomatitis (RAS) is a common oral disorder that despite extensive"nresearches, the etiology of this phenomenon is still unknown. Because this phenomenon has been observed"nmore often in families than in individual cases, genetic influence has been investigated in most researches."nPurpose: The aim of the present study was to evaluate the association between Human Leukocyte Antigen"n(HLA) and aphthous stomatitis more precisely."nMaterials and Methods: in this study, 60 patients with RAS were examined for HLA-A and HLA- B types"nand 37 of them were examined for HLA- DR and HLA-DQ types. The results were compared through Fisher"ntest with those of 25 healthy control subjects, aged more than 30 years."nResults: A significant decrease in the frequency of some antigens such as HLA-DQW 3 and HLA-A 26 in"nsubjects with RAS was observed. Therefore, according to the results of this study, these antigens were"nconsidered as resistant antigens to recurrent aphthous stomatitis. In contrast, there was no significant increase"nin the frequency of any HLA antigens in the test group, compared to the control group. This finding is in"ncontrast with the multiple reports about Behcet's disease. (Because a high frequency of HLA-B 51 has been"nfound in Behcet's syndrome.)"nConclusion: According to the findings of this study, it is suggested that the pathogenicity of aphthous"nulcerations in Behcet's disease and recurrent aphthous stomatitis is not the same. However, further studies are"nnecessary to prove this theory.